Mortality in 98 type 1 diabetes mellitus and type 2 diabetes mellitus: Foot ulcer location is an independent risk determinant. Issue 10 (14th June 2021) - Schofield, Heather; Haycocks, Samantha; Robinson, Adam; Edmonds, Michael; Anderson, Simon G; Heald, Adrian H.
Abstract: Introduction: We previously demonstrated in both a longitudinal study and in meta‐analysis (pooled relative‐risk RR, 2.45) that all‐cause mortality is significantly higher in people with diabetes foot ulceration (DFU) than with those without a foot ulcer. In this prospective study, we looked at the factors linked to mortality after presentation to podiatry with DFU. Methods: Ninety‐eight individuals recruited consecutively from the Salford Royal Hospital Multidisciplinary Foot Clinic in Spring 2016 were followed up for up to 48 months. Data concerning health outcomes were extracted from the electronic patient record (EPR). Results: Seventeen people (17) had type 1 diabetes mellitus, and 81 had type 2 diabetes mellitus. Thirty‐one were women. The mean age (range) was 63.6 (28–90) years with maximum diabetes duration 45 years. Mean HbA1c was 72 (95% CI: 67–77) mmol/mol; 97% had neuropathy (International Working Group on the Diabetic Foot (IWGDF) monofilament); 62% had vascular insufficiency (Doppler studies); 69% of ulcers were forefoot, and 23% of ulcers were hind foot in location. Forty of 98 (40%) patients died in follow‐up with 27% of death certificates including sepsis (not foot‐related) and 35% renal failure as cause of death. Multivariate regression analysis indicated a 6.3 (95% CI: 3.9–8.1) fold increased risk of death with hind foot ulcer, independent of age/BMI/gender/HbA1c/eGFR/total cholesterol level. Conclusion: This prospective study has indicated a very high long‐term mortality rate in individuals with DFU, greater for those with a hind foot ulcer and shown a close relation between risk of sepsis/renal failure and DFU mortality, highlighting again the importance of addressing all risk factors as soon as people present with a foot ulcer.